Da Saramago a Cechov: il teatro musicale di Azio Corghi e il “teatro epico” del ‘900 (Itinera, 2013)
Since his debut, in Gargantua (1984, by François Rabelais), and even more in the works composed in collaboration with José Saramago (Blimunda, 1990; Divara, 1993), Azio Corghi has pursued an idea of drama characterized by a marked ‘aesthetic presence’ of the author and by his vision of the world, typical of the ‘epic’ theatre of the twentieth century. In 2000, composing Tat’jana Repina (2000) by Chekhov, with his ‘open’ theatricality and tormented existential problems, the musician was forced to rethink his musical dramaturgy: the landscapes of History designed by Saramago are replaced by a psychological story, which takes place in a ‘community’ of individuals marked by loneliness and despair; and the choral, ‘collective’ dimension, which in Blimunda and Divara arose from History, is converted into a ‘monological’ chorus which is typically Chekhovian and shows the crisis of communication typical of the modern theatre. To convey the bleak pessimism of Chekhov, in Tat’jana – going beyond Blimunda and Divara’s predominant symbolism – Corghi pushed his writing to the highest level of abstraction, used only at the beginning, during his structuralist period, no more in accordance with the strict determinism of post-Webern avant-garde but according to a free choice, dictated by inner artistic necessity.